Polymer Biodegradation and Polymeric Biomass Valorization - Bulak, Piotr (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Polymer Biodegradation and Polymeric Biomass Valorization" is devoted to the current trends in research on the biodegradation of waste polymer materials, both of natural (cellulose and chitin) and artificial origins. New methods of management and valorization in accordance with the hierarchy of the waste pyramid by means of new methods and technologies, as well as the development of new bioremediation techniques, are also of interest to this reprint. In addition, recycling, recovery, and ways to produce and research new environmentally friendly polymeric materials are at the center of interest.